The Associations Between Gonadal Hormones and Serum Uric Acid Levels in Men and Postmenopausal Women With Diabetes - Wan, Heng; Zhang, Kun; Wang, Yuying; Chen, Yi; Zhang, Wen; Xia, Fangzhen; Zhang, Yunping; Wang, Ningjian; Lu, Yingli (Frontiers in Endocrinology, 2020)
Introduction: In assessing the development of hyperuricemia in diabetic adults, the role of the sex steroid axis is underappreciated. Furthermore, dehydroepiandrosterone (DHEA) has been recommended as a nutritional supplement. However, is DHEA suitable for diabetic adults with hyperuricemia? This issue has received little attention. Aim: The objective of this study was to investigate the associations between gonadal hormones and uric acid (UA) levels in diabetic adults, especially the association between DHEA and UA levels. Methods: We analyzed 4,426 participants out of 4813 diabetic adults enrolled from seven communities in a cross-sectional survey conducted in 2018. Participants underwent several examinations including the anthropometric parameters, blood pressure, glucose, lipid profiles, UA, total testosterone (TT), estradiol (E2), follicle-stimulating hormone (FSH), luteinizing hormone (LH) and dehydroepiandrosterone (DHEA). Results: Among men, compared with individuals in the first quartile, participants in the fourth quartile of TT and FSH had odds of hyperuricemia that were significantly decreased by 48% and 34% (both P <0.05). However, participants in the fourth quartile of DHEA had 79% increased odds of hyperuricemia (P <0.05). Among postmenopausal women, participants in the fourth quartile of DHEA, TT and LH had odds of hyperuricemia that were significantly increased by 155%, 99% and 76% (all P <0.05). These associations were adjusted for potential confounding factors. Conclusions: Sex differences were found in the associations between gonadal hormones and UA levels in diabetic men and postmenopausal women, which should be monitored to prevent hyperuricemia when sex hormone treatment, especially DHEA, is administered. Further studies are needed.